The intention of private companies to pay business zakat: A study in Kedah - Mohamad Zaidi, Azizan (2023)
The global economy recession during and post COVID-19 has been impacted to all sectors business. This situation will definitely have an impact on the collection of business zakat by all State Zakat Centers in Malaysia. Using the Theory of Planned Behaviour, this study revealed whether the theoretical foundations could explain the tendency of payers in discharging business zakat more clearly. This study aimed to examine the influencing factors to the tendency of the payer. The factors examined in this study were attitude, subjective norms, trust, and knowledge of zakat. A total of 254 questionnaires were distributed to entrepreneurs and 108 questionnaires were answered by private companies which were used for further analysis. Questionnaires were distributed through ‘google forms’ via WhatsApp application and email to business zakat payers. This study had used the analytical methods including independent T Test, One -Way Analysis of Variance (ANOVA), Pearson Correlation and Multiple Regression. Finally, this research concluded with suggestions and recommendations that can help private companies to have the tendency to pay business zakat by following the correct zakat calculation. Among the recommendations was that the Lembaga Zakat Negeri Kedah (LZNK) and the Government should assist in raising awareness of the obligation to pay zakat to the public, especially for business zakat. This study demonstrated that all independent variables have a relationship with the dependent variable. However, it was discovered in this study that the two (2) independent variables that had the significant influence on the dependent variables were attitude and knowledge of zakat.